Accidental Low-Velocity Penetrating Brain Injury by Glass Marble - Woo, Xiangling; Yap, Nelson Kok Bing; Toh, Teck Hock; Yiek, Siew Hong (Asian Journal of Neurosurgery, 2022)
Penetrating brain injury from marble is rare. Marbles, commonly known as “guli” among locals, is a popular children's traditional game in Malaysia. This study discusses two cases of intracranial marble injury, both accidentally shot by children with home-made air guns during the period of Movement Control Order with one elderly patient who passed away. While the diagnosis was uneventful, the management was not straightforward. Strategies of prehospital, operative, postoperative management, and rehabilitation are discussed, including prognostic factors. Because of its rarity, the management of such injuries is complex and nonstandardized.
Keywords: Keywords; penetrating brain injury; low-velocity; intracranial injury